2009
DOI: 10.1530/rep-09-0082
|View full text |Cite
|
Sign up to set email alerts
|

CD9 regulates transcription factor GCM1 and ERVWE1 expression through the cAMP/protein kinase A signaling pathway

Abstract: ERVWE1 (SYNCYTIN-1), a membrane protein originating from the envelope gene of human endogenous retrovirus-W (HERV-W), mediates the fusion of mononucleated cytotrophoblasts into multinucleated syncytiotrophoblast. Though ERVWE1 has been characterized since its discovery, regulatory mechanisms associated with ERVWE1 expression have not been firmly established. We hypothesized that membrane protein CD9, involved in cell-cell fusion of fertilization and myogenesis, could be involved in the regulation of ERVWE1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Cyclic AMP treatment has long been known to promote fusion of both primary human cytotrophoblasts [30] and BeWo cells [24], [25], and to upregulate several proteins involved in fusion, including syncytin-1 [31], syncytin-2 [32], MFSD2A [33] and CD9 [34]. In the present study, treatment of BeWo cells with the cell-permeable cAMP analogue dbcAMP led to an upregulation of RhoE, concomitant with an increase in cell fusion.…”
Section: Discussionsupporting
confidence: 50%
“…Cyclic AMP treatment has long been known to promote fusion of both primary human cytotrophoblasts [30] and BeWo cells [24], [25], and to upregulate several proteins involved in fusion, including syncytin-1 [31], syncytin-2 [32], MFSD2A [33] and CD9 [34]. In the present study, treatment of BeWo cells with the cell-permeable cAMP analogue dbcAMP led to an upregulation of RhoE, concomitant with an increase in cell fusion.…”
Section: Discussionsupporting
confidence: 50%
“…Splicing efficiency has not been studied at all in cancer-specific aberrant expression of other HERV families. Third, the trophoblastic expression of ERVWE1 is controlled from a juxtaposed trophoblast-specific enhancer localized in MaLR LTR [9] and requires stimulation by certain tissue-specific transcription factors, such as GCM1 [10, 39], whose activity could be studied in germ line tumors. In neither type of tumors described in this study, we observed GCM1 expression comparable with placenta or BeWo cells, which points to the critical importance of promoter demethylation as a prerequisite for ERVWE1 transcriptional de-repression.…”
Section: Discussionmentioning
confidence: 99%
“…[39]) and inducible expression of HERV-K rec gene in mice led to a disturbance of germ cell development reminiscent of early seminoma [40]. Genome-wide comparison of HERV expression in testicular cancer and normal testicular tissue has been done using copy-specific microarray and several HERV copies of families E, H, K, and W were found to be differentially expressed in testicular tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A multispanning membrane protein, CD9, was identified as a regulator for GCM1 gene (Muroi et al . ). This protein is involved in the invasive regulation of cancer cells, and in cell fusion between sperm and egg as well as myoblasts (Tachibana & Hemler ; Le Naour et al .…”
Section: Placenta Ervsmentioning
confidence: 97%
“…CD9 is another upstream factor controlling GCM1 and syncytin genes (Muroi et al . ). Just as in humans, GCM1 controls the expression of mouse syncytin A and syncytin B genes (Schubert et al .…”
Section: Hypothesis Of Gene Evolution Through Baton Passmentioning
confidence: 97%